Spectra of generalized stochastic adding machines - Messaoudi, Ali [UNESP]; Valle, Glauco (Institute of Mathematics, Polish Academy of Sciences, 2018)
We define stochastic adding machines based on Cantor systems of numeration. We show that the spectra associated to these stochastic adding machines are fibered Julia sets, and we also compute various parts of the spectra of their transition operators in different Banach spaces, like c0, c and lα, 1 ≤ α ≤ 1.
Keywords: Cantor systems of numeration; Julia sets; Markov chains; Spectrum of transition operator; Stochastic adding machines